Implementation of Service Recovery on Behavioral Intentions through Perceived Value in Banking Services During the Covid 19 Pandemic - Syarif Hidayatullah; Ryan Gerry Patalo; Ery Sulistyorini (Jurnal Keuangan dan Perbankan, 2022)
Banking is a financial intermediary or liaison institution whose activities are aimed at collecting funds from the wider community (clients) and distributing them to people in need of funds. So that customer needs can be met and bank growth and bank financing can be increased. The Covid-19 virus pandemic has affected several activities, including the banking sector. Therefore, in order for the banking sector to continue to operate and survive in the midst of the corona virus pandemic, banks must be able to mitigate risks appropriately and carefully, as well as employ a variety of innovative strategies in the current uncertainty. Objectives of this study: 1. To identify and analyze the impact of partial and simultaneous service recovery and perceived value on behavioral intentions at BNI Malang, 2. To identify and analyze the indirect impact of service recovery on behavioral intention through perceived value in BNI Malang. The type of research used is explanatory research. With the study site at BNI Malang, the study targets are people who have been at BNI Malang. The population in this study was 100 respondents. The data analysis methodology used quantitative descriptive analysis and path analysis.